Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00044-010-9353-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preliminary evaluation of 2-substituted-1,3-benzoxazole and 3-[(3-substituted)propyl]-1,3-benzoxazol-2(3H)-one derivatives as potent anticancer agents

Abstract: The synthesis and cytotoxic activity studies of a new series of cyclic amine containing benzoxazole and benzoxazolone derivatives are described. The 2-cyclic amine-1,3-benzoxazoles 5a-k, 5-chloro-3-(3-chloropropyl)-1,3-benzoxazol-2(3H)-one 8 and 3-[3-(cyclic amino)-propyl]-1,3-benzoxazol-2(3H)-ones 9a-f were synthesized. The newly synthesized compounds with the influence of the presence of cyclic amine moiety in the benzoxazole scaffold have been evaluated with respect to their cytotoxic effect toward four hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…Compound 69 was reported as the most potent growth inhibitor of MDA-MB-468, a triple negative/basal-like breast carcinoma cell line [140]. Amongst the compounds developed by Murty et al, compound 70 was reported as the most active compound of the series [141]. Amongst the compounds synthesized by Mallesha et al, compound 71 emerged as the most potential anticancer agent [142].…”
Section: Analgesic and Anti-inflammatory Activitymentioning
confidence: 96%
“…Compound 69 was reported as the most potent growth inhibitor of MDA-MB-468, a triple negative/basal-like breast carcinoma cell line [140]. Amongst the compounds developed by Murty et al, compound 70 was reported as the most active compound of the series [141]. Amongst the compounds synthesized by Mallesha et al, compound 71 emerged as the most potential anticancer agent [142].…”
Section: Analgesic and Anti-inflammatory Activitymentioning
confidence: 96%
“…Pyridazin-3(2h)-one derivatives constitute an interesting class of heterocyclic lead compounds for drug discovery and research into anticancer molecules [15][16][17]. Recently, it was reported that some pyridazin-3(2h)-one derivatives specifically interact with and inhibit PIM (potential tumor targets) kinases with low nanomolar potency [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Benzoxazolone derivatives are an important class of heterocyclic compounds widely studied in medicinal chemistry because they show a broad spectrum of activity against Gram-positive and Gram-negative bacteria and fungi [2][3][4][5][6][7][8], human immunodeficiency virus (HIV)-1 reverse transcriptase [9] and multidrug-resistant cancer cells [10,11]. Various derivatives of benzoxazolone are commercially available, for example, benzolon 1 (myorelaxant), paraflex 2 (sedative anelgesic) and vinizene 3 (topical antiseptic) [12].…”
Section: Introductionmentioning
confidence: 99%